Samnyong the mute = 벙어리 삼룡이 - Na, To-hyang 1902-1927; Park, Sunyoung; 박선영 (Seoul Asia Publishers(아시아), 2015)
Samnyong is a typical subaltern in Chosǒn during Japan's colonial period - a character robbed of his voice. The story's literary achievement lies in the process in which the subaltern's repressed sexual desire blooms, while his rage at the class system explodes.
한영대역본임. Texto paralelo en coreano e inglés con texto en inglés en páginas opuestas.
Keywords: Novela coreana; Literatura coreana - -- Siglo XX